2019
DOI: 10.1016/j.surfcoat.2018.10.026
|View full text |Cite
|
Sign up to set email alerts
|

The tribological properties of short range ordered W-B-C protective coatings prepared by pulsed magnetron sputtering

Abstract: The tribological properties of short range ordered W-B-C protective coatings prepared by pulsed magnetron sputtering Debnarova, S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
6
6
0
Order By: Relevance
“…The Er measured in our films follow the same trends previously described for hardness, see Fig. 8a and 8b, with the highest value of ~ 280 GPa for the film deposited with 10 sccm TMB at 500 o C and a lowest value of ~130 GPa for the film deposited at 900 o C. Similar as for the hardness, our Er ~ 280 GPa value is similar to the Er ~ 300 GPa reported by Debnárová et al [27] but lower than the ~ 450 GPa reported in the studies by Alishahi et al [26]. Furthermore, for W2C and WC1-x films containing 35 at.% C Palmquist et al [14] measured an E-moduli of ~ 450 GPa, i.e.…”
Section: Mechanical Propertiessupporting
confidence: 90%
See 2 more Smart Citations
“…The Er measured in our films follow the same trends previously described for hardness, see Fig. 8a and 8b, with the highest value of ~ 280 GPa for the film deposited with 10 sccm TMB at 500 o C and a lowest value of ~130 GPa for the film deposited at 900 o C. Similar as for the hardness, our Er ~ 280 GPa value is similar to the Er ~ 300 GPa reported by Debnárová et al [27] but lower than the ~ 450 GPa reported in the studies by Alishahi et al [26]. Furthermore, for W2C and WC1-x films containing 35 at.% C Palmquist et al [14] measured an E-moduli of ~ 450 GPa, i.e.…”
Section: Mechanical Propertiessupporting
confidence: 90%
“…This is a consequence of the reaction between the Si(100) substrate and the film, resulting in formation of WSi2 at 700 and 800 o C or a Si rich surface at 900 o C as determined from our XRD and XPS measurements and where the reaction also yields an increased surface roughness seen from the loss of the silver-white color and metallic luster. The H varies in the range 23 to 31 GPa for films deposited with different TMB flows and at temperatures ≤ 600 o C; a closer inspection shows the lowest H values for the films deposited at temperatures of 200, 300 and 400 o C, with H = 23, 25, and 24 GPa, respectively.Our H values are comparable or even slightly higher than the reported HV of d-WC with 22 GPa for a 0001-oriented single-crystal[2] as well as to those reported for more carbon and boron rich W-B-C films by Alishahi et al[26] and Debnárová et al[27] with values in the range ~24 to ~29 GPa and ~23 GPa, respectively. In contrast, our H values are lower than the ~37 to ~47 GPa reported by Su et al[24] for d-WC films alloyed with ~4 to ~7 at.…”
supporting
confidence: 89%
See 1 more Smart Citation
“… 10 13 Some other temperature-adaptive lubricating materials allowing for diffusion-based and/or oxidation-based mechanisms can be potentially used over multiple thermal cycles in microlaminate architectures; 1 , 5 , 11 , 13 18 their metal or transition-metal suboxides including the so-called Magnéli phases (e.g., TiO x , MoO x , VO x , and WO x ) are suitable as middle temperature range lubricants. 11 , 12 , 19 , 20 Ceramic-enhanced coatings (particularly when comprising Ag) have been found to further lift the temperature threshold; yet, they generate higher coefficient of frictions (CoFs) (>0.2–1). 13 , 16 , 17 , 21 , 22 …”
Section: Introductionmentioning
confidence: 99%
“…Later, an ab-initio modeling of similar materials was performed and it was reported that crystalline Ta 2 BC and W 2 BC in particular are also promising candidates for experimental synthesis owing to their calculated elastic properties indicating their simultaneous high stiffness and moderate ductility [13]. Although experimental studies of coating systems like Ti-B-C [14][15][16][17][18][19][20], Ta-B-C [21], Nb-B-C [22], and W-B-C [19,[23][24][25][26][27][28] potentially leading to the formation of the X 2 BC crystalline structure have been published, no formation of the ternary crystalline X 2 BC phase other than Mo 2 BC has ever been reported [11,13].…”
Section: Introductionmentioning
confidence: 99%